-3-7=-4+x

Simple and best practice solution for -3-7=-4+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-7=-4+x equation:


Simplifying
-3 + -7 = -4 + x

Combine like terms: -3 + -7 = -10
-10 = -4 + x

Solving
-10 = -4 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-10 + -1x = -4 + x + -1x

Combine like terms: x + -1x = 0
-10 + -1x = -4 + 0
-10 + -1x = -4

Add '10' to each side of the equation.
-10 + 10 + -1x = -4 + 10

Combine like terms: -10 + 10 = 0
0 + -1x = -4 + 10
-1x = -4 + 10

Combine like terms: -4 + 10 = 6
-1x = 6

Divide each side by '-1'.
x = -6

Simplifying
x = -6

See similar equations:

| 9-(2n-6)=5-3n | | -7-3=8x+4-7x | | 1.4y=4.62 | | 9x+8-8x=13 | | X(2x+3)=(2x+5)(x-1) | | (x/50)=-11+25 | | x+12527=215+12527 | | 2+2.99999999999999999+0.1=n | | 6/5x^2+7x-70=0 | | -14+10=m-3 | | x-12527=215-12527 | | 2a+6=5a-30 | | 16(2x-1)=4(8x+9) | | 40-x=72 | | 2.561x=-12.36963 | | 2[7-5(1-n)]+5n=-6+2[6(n+1)-3n] | | 4y+y=6y-4y | | -(5x-3)-(4x-7)+6=-7(x-4)-(9x+5)+8 | | 8b+20=9b-6 | | 2x^3=384 | | (-3/-4) | | 4(x+5)=2(2x+1)+18 | | 1/4*(x+3)=4x-2(x-3) | | 13-(2f+2)=2(f-2)+3f | | 7(-4+6x)= | | 5x+17y=-13 | | -2+7=15 | | 49x^2+36y^2=1 | | 7x-2(x-2)=5(x+1)+4 | | 6x+8/15x+20 | | 6(2x-5)=2(6x+1) | | 3(x+5)=2(x-6)+x |

Equations solver categories